MUTU GULA AREN (Arenga pinnata Merr) DI PASAR KOTA BANDA ACEH (The Palm (Arenga pinnata merr) Sugar Quality In Banda Aceh Market) - Muzaifa, Murna; Juanda, Juanda; Rinaldi, Rinaldi (Jurnal Hasil Penelitian Industri, 2013)
The aim of this research was to study the quality of arenga palm sugarespecially solid sugar at several markets in Banda Aceh. The research was conducted bysurvey using purposive random sampling method with proportional samples. Five marketschosen are Peunayong, Aceh, Seutui, Kampong Ateuk and Lamnyong. The total number ofpalm sugar traders who spread in the five markets are about 40 peoples. This researchsecured 8 traders as respondents. Needed palm sugar about 1 kilogram for analyses thereal quality. The parameters analyzed include moisture content, insoluble in water, ashcontent and reducing sugar levels. The data analyzed by using histogram and the dataanalysis were made by using SPSS program. The result showed the average moisturecontent and reduced sugar content has met the SNI 01-3743-1995, whereas the insolublematerial and ash content did not have any specifications yet. The average of moisturecontent of the palm sugar were 4,01%, the reduction palm sugar were 7,78%, the insolublematerials were 1,34% and ash content were 2,58%. The palm sugar parameter which mostunspecific materials were the insoluble for 87,5%.